Path creation in Nordic energy and road transport systems – The role of technological characteristics. (April 2017) - Hansen, Teis; Klitkou, Antje; Borup, Mads; Scordato, Lisa; Wessberg, Nina
Abstract: This paper reviews path-creation processes in road transport systems in the Nordic countries: e-mobility in Denmark, hydrogen and fuel-cell electrical vehicles in Norway, and advanced biofuels in Finland and Sweden. The study builds on the path creation literature, which seeks to explain the emergence of new technological pathways. Drawing on recent insights concerning the differences between design- and manufacturing-intensive technologies, the paper analyses the influence of technological characteristics on path creation processes. The case comparison indicates that technological characteristics seem to have greater influence on the content of activities in the later phase rather than the early phase of path creation processes. The analysis also emphasises that barriers to path creation processes differ depending on technological characteristics. This highlights the importance of considering technological characteristics in energy and transport policies.